2021
DOI: 10.3389/fpsyg.2021.711669
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Child Attachment and Social Adaptation Behavior in Chinese College Students: The Mediating Role of School Bonding

Abstract: Family and school are two main places for adolescents to develop socialization, which can be contributed by good parent-child attachment and school bonding. Earlier studies suggested that parent-child attachment played an important role in promoting the formation of high-level school bonding, which is also likely to influence social adaptation. This study aimed to explore the relationship between parent-child attachment and social adaptation, and the mediating role of school bonding. Using stratified cluster s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…Furthermore, this study found that father-child attachment significantly affected college students’ sense of school belonging, and sense of school belonging partially mediates the relationship between father-child attachment and academic burnout, supporting Hypothesis 3. This finding is in line with previous research on the relationship between parent–child attachment and school belonging ( Yin et al, 2021 ). In traditional Chinese families, fathers serve as role models, and children often mimic their fathers’ behaviors and ways of handling things, forming a set of patterns during interactions with their fathers.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, this study found that father-child attachment significantly affected college students’ sense of school belonging, and sense of school belonging partially mediates the relationship between father-child attachment and academic burnout, supporting Hypothesis 3. This finding is in line with previous research on the relationship between parent–child attachment and school belonging ( Yin et al, 2021 ). In traditional Chinese families, fathers serve as role models, and children often mimic their fathers’ behaviors and ways of handling things, forming a set of patterns during interactions with their fathers.…”
Section: Discussionsupporting
confidence: 93%
“…To date, the external factors influencing academic burnout among college students have received less attention from researchers compared to individual internal factors, with limited research focusing on key external factors such as family and school. Father-child attachment and mother–child attachment, as one of the most important proximal environmental factors, provide a solid foundation for individuals’ cognitive development and significantly influence their social adaptation ( Yin et al, 2021 ). A few studies have confirmed the impact of parent–child attachment on learning burnout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an effective way to gain positive emotions and assistance, and it plays an important role in psychological responses. 9 The changes in physiological function affect a person's perceptions, experiences and adaptation levels, which means that frailty levels may also influence PSS. Therefore, this study made the hypothesis that PSS is correlated with frailty and SPB.…”
Section: Introductionmentioning
confidence: 99%
“…32 or modified it slightly, "defining the 'other significant person' dimension in the scale exactly as 'teacher and classmates', to refer to the support from both teachers and classmates". 35,36 However, for students, "support from teachers and support from classmates" obviously cannot be confused, and there is also no revision on the scale text. In addition, some research notes use the version revised by Huang et al, 31 but their interpretation of the three factors of the scale is not consistent with the original one; 37 or the introduction of the Chinese version of the social support scale adopted in its text is not enough, or the structure of the scale is inconsistent with that of the original scale 38,39 and so on.…”
mentioning
confidence: 99%